Characterization of rhizosphere bacterial communities in oilseed rape cultivars with different susceptibility to Plasmodiophora brassicae infection - Deng, Yue; Wu, Wenxian; Huang, Xiaoqing; Yang, Xiaoxiang; Yu, Yaoyin; Zhang, Zhongmei; Hu, Zijin; Zhou, Xiquan; Zhou, Kang; Liu, Yong; Zhang, Lei (Frontiers in Plant Science, 2025)
Rhizosphere microbiomes are constantly mobilized during plant–pathogen interactions, and this, in turn, affects their interactions. However, few studies have examined the activities of rhizosphere microbiomes in plants with different susceptibilities to soil-borne pathogens, especially those that cause clubroot disease. In this study, we compared the rhizosphere bacterial community in response to infection of Plasmodiophora brassicae among the four different clubroot susceptibility cultivars of oilseed rape (Brassica napus). Our results revealed obvious differences in the responses of rhizosphere bacterial community to the P. brassicae infection between the four cultivars of oilseed rape. Several bacterial genera that are associated with the nitrogen cycle, including Limnobacter, Thiobacillus, Anaeromyxobacter, Nitrosomonas, Tumebacillus, and Halomonas, showed significantly different changes between susceptible and resistant cultivars in the presence of P. brassicae infection. Moreover, increased connectedness and robustness were exhibited in the rhizosphere bacterial community co-occurrence network in clubroot-susceptible cultivars that were infected with P. brassicae, while only slight changes were observed in clubroot-resistant cultivars. Metagenomic analysis of microbial metabolism also indicated differences in the rhizosphere bacterial community between susceptible and resistant cultivars that were infected with P. brassicae. Functional analysis of the nitrogen cycle showed that genes related to nitrification (nxrB) were upregulated in susceptible cultivars, while genes related to assimilatory nitrate reduction (nasA, narB, and nirA) were upregulated in resistant cultivars that were infected with P. brassicae. These findings indicate that the synthesis and assimilation process of NO3- content were promoted in susceptible and resistant cultivars, respectively. Our study revealed differences in the characteristics of rhizosphere bacterial communities in response to P. brassicae infection between clubroot-susceptible and clubroot-resistant cultivars as well as the potential impact of these differences on the plant–P. brassicae interaction.